Cervical Vestibular-Evoked Myogenic Potentials in Sedated Toddlers - Ibraheem, Ola Abdallah; Hassaan, Mohammad Ramadan (International Archives of Otorhinolaryngology, 2018)
Introduction Cervical vestibular-evoked myogenic potentials (cVEMPs) are difficult to test in toddlers who cannot follow instructions or stay calm.Objective Due to the growing need for vestibular testing in very young children as a part of a delayed walking assessment battery, this study aimed to provide a solution to this problem by recording the cVEMPs in toddlers during sedation.Method The cVEMPs measures were assessed in 30 toddlers aged 12 to 36 months with normal motor milestones. They were sedated with chloral hydrate. Then, the head was retracted ∼ 30° backward with a pillow under the shoulders, and turned 45° contralateral to the side of stimulation to put the sternocleidomastoid (SCM) muscle in a state of tension.Results The P13 and N23 waves of the cVEMPs were recordable in all sedated toddlers. The cVEMPs measures resulted in the following: P13 latency of 17.5 ± 1.41 milliseconds, N23 latency of 25.58 ± 2.02 milliseconds, and peak-to-peak amplitude of 15.39 ± 3.45 µV. One-sample t-test revealed statistically significant longer latencies and smaller amplitude of the toddlers' cVEMPs relative to the normative data for adults.Conclusions The difficulty of cVEMPs testing in toddlers can be overcome by sedating them and attaining a position that contracts the SCM muscle. However, the toddlers' recordings revealed delayed latencies and smaller amplitudes than those of adults.
Keywords: cervical vestibular-evoked myogenic potentials; chloral hydrate; saccule